PROSES PENETRASI SOSIAL PENGGUNA HORNET DI KARAWANG - Oktaviani, Violita; Nursanti, Siti; Nayiroh, Luluatu (HERITAGE, 2024)
This research aims to determine the approach process carried out by Gay Homosexuals in Karawang in their efforts to establish same-sex relationships in private through a Gay online dating application called Hornet, which is expected by users to foster interpersonal communication to establish relationships like normal relationships in general. . The method used in this research is a descriptive method with a qualitative research approach assisted by observation and interviews in data collection and documentation as supporting data in this research. The results of this research show that informants prove the effectiveness of the Hornet application in the success of the Gay relationships they build by going through several phases of the illustration of the theory of social penetration in interpersonal communication. However, it does not rule out the possibility that gay couples who are successful in establishing a relationship will encounter obstacles caused by internal and external factors.